1969
DOI: 10.1139/m69-077
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous production of three phenazine pigments by Pseudomonas aeruginosa Mac 436

Abstract: Pseudomonas aeruginosa Mac 436 was found to produce simultaneously three phenazine pigments identified as pyocyanine, phenazine-1-carboxylic acid, and oxychlororaphine. Production of these pigments on various media indicated a wide variation in yields depending on the composition of the media, but satisfactory yields of all three pigments were obtained. A scheme was developed for separation and assay of the pigments from the culture liquor. Details of production, isolation, assay, and identification are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…The structural features and spectral properties of the antibiotic isolated from P. fluorescens are similar to those of the antibiotic tubermycin B (phenazine-1-carboxylic acid) (2). However, the solubility properties, molecular weights, I II VOL.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…The structural features and spectral properties of the antibiotic isolated from P. fluorescens are similar to those of the antibiotic tubermycin B (phenazine-1-carboxylic acid) (2). However, the solubility properties, molecular weights, I II VOL.…”
Section: Methodsmentioning
confidence: 82%
“…A fragment at mlz 360 strongly suggests the existence of a dimer. The existence of a phenazine moiety in the antibiotic molecule is further supported by a strong absorption peak at 251 nm accompanied by a broad peak at 364 nm (with shoulders at 353 and 409 nm), and also by the infrared bands at 860 and 840 cm-' (2).…”
Section: Methodsmentioning
confidence: 90%
“…Strains of P. aeruginosa have been shown to vary in the timing and extent of phenazine production relative to the growth phase (9,10,18). We have observed that the appearance of pyocyanin in wild-type P. aeruginosa PA14 LB cultures correlates with entry into stationary phase and that pyocyanin production plateaus in late stationary phase, reaching concentra-FIG.…”
Section: Resultsmentioning
confidence: 91%
“…Chorismic acid has long been recognized as the branch point from the shikimic acid pathway to phenazine synthesis (26). Studies with radiolabeled precursors suggest that the phenazine core is formed by the symmetrical condensation of two molecules of chorismic acid (7,20,22,26), while the amide nitrogen of glutamine serves as the immediate source of nitrogen in the heterocyclic nucleus of phenazine compounds (36). Phenazine-1,6-dicarboxylic acid is the first phenazine formed, and it is thought to be converted to phenazine-1-carboxylic acid (PCA), a key intermediate in the synthesis of other phenazines by fluorescent pseudomonads (6,20,22,28).…”
mentioning
confidence: 99%